The Renaissance and Refashioning of Skills-Based Pay for the 2020s: Learning From the UK - Brown, Duncan; Armstrong, Michael (Compensation and benefits review, 2025)
Skill-based pay (SBP) has had a long but chequered history. However, interest in it has intensified recently in the UK, largely as a result of labour shortages and increasing and often unsatisfied demands for skills, which prevailing market-driven approaches to compensation have failed to address. It has become evident that SBP can provide a useful means of supporting organisations to attract, retain, develop and engage the increasing numbers and range of skilled people they need to grow and succeed. In this article we describe the current context within which SBP is being developed; review the historical development of the approach and then illustrate the increasingly varied range of methods now being taken to how SBP is being applied in the UK; and draw some tentative conclusions from our analysis for SBP’s practical application, along with implications for future research.